STRUKTUR KOMUNITAS IKAN AIR TAWAR YANG DITEMUKAN DI SUNGAI LUBUK BAKONG TUA TUNU PANGKALPINANG - Rama Supanji; Wahyu Adi; Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2018)
The Lubuk Bakong’s River is located in Tua Tunu Village, Pangkalpinang and generally used as agricultural land and livestock. The purpose of this research is to analyze the community structure and the relationship of aquatic parameters to the diversity of fish in the Lubuk Bakong River. The benefit of this research is to complete data about the structure of the fish community in the Lubuk Bakong River. This research was conducted in March 2018 at the Lubuk Bakong River, Tua Tunu Village. Sample identification was carried out at the Fisheries Laboratory, FPBB. The method used is purposive sampling method and Principal Component Analysis. The fishes caught are Kemuring (Puntius lineatus), Tanah (Puntius binotatus), Palm (Osteochilus spilurus), Seluang (Rasbora cepholotaenia), Ordinary septic (Trichogaster trichopterus), Belida (Chitala sp), Betok (Anabas testudineus), Kelincah (Belontia hasselti), Kepatung (Pristolepis grootii), Baung (Mystus nemurus), Gabus (Channa striata), Kiung (Channa lucius), Sepat api (Trichogaster pectoralis) and Chitala sp. The results of the analysis related characteristics of environmental parameters on the diversity of fish species show the magnitude of the effect of the parameters Depth, Current velocity, and Nitrate at station I, station II shows the magnitude of the influence of temperature, pH, DO, Brightness, and Nitrate parameters and station III is more influenced by Phosphate factors